The Effect of Hemodialysis Therapy on Blood Glucose Levels in Patients in the Hemodialysis Room Prof. Dr. H. Aloei Saboe General Hospital Gorontalo City - Nurhayti Abudi Ali; Nasrun Pakaya; Gusti Pandi Liputo (Universitas Muhammadiyah Palu, 2026)
Hemodialysis generally functions to remove metabolic waste products that cause a decrease in blood glucose levels. The purpose of this study was to determine the effect of hemodialysis therapy on blood glucose levels in patients in the hemodialysis room at Prof. Dr. H. Aloei Saboe Regional General Hospital in Gorontalo City. The research method used was quantitative research with a quasi-experimental design and a one-group pre-post test design. The sample consisted of 26 respondents using purposive sampling technique. The Wilcoxon test yielded a p-value of 0.000 (p-value < 0.05), indicating that hemodialysis therapy affects blood glucose levels in patients in the hemodialysis room at Prof. Dr. H. Aloei Saboe Regional General Hospital in Gorontalo City. Hemodialysis therapy can reduce the burden of uremic toxins that previously interfered with insulin sensitivity. After dialysis, cellular response to insulin improves, allowing blood glucose levels to be controlled more effectively. It is hoped that this will yield positive results in enhancing the quality of nursing care for patients undergoing hemodialysis therapy, particularly in measuring blood glucose levels. Hemodialysis therapy should be performed to measure blood glucose levels.